SISTEM PAKAR DIAGNOSA PENYULIT MENYUSUI MENGGUNAKAN METODE CERTAINTY FACTOR - Nurhayati Nurhayati; Siti Farida (STMIK KAPUTAMA, 2021)
ABSTRACT Breastfeeding is a mother's natural nature after giving birth, but there are many obstacles that make it difficult for mothers to breastfeed their babies, both from the baby and the mother's own physiology. Lack of knowledge of mothers causes mothers to not be able to recognize the physical changes that become obstacles in breastfeeding. This study aims to develop an expert system that is able to diagnose breastfeeding difficulties by applying the certainty factor method. The stages of developing an expert system include needs analysis, data collection, knowledge acquisition, knowledge representation, design and implementation. The accuracy test with the confusion matrix is used to determine the level of accuracy of the developed expert system. As a result, the expert system has been able to accurately and validly diagnose the symptoms of breastfeeding difficulties.Keyword: Expert system, Certainty Factor, Breastfeeding ABSTRAK Menyusui merupakan kodrat alamiah ibu setelah melahirkan, tetapi ada banyak kendala penyulit ibu menyusui bayi, baik dari bayi maupun fisiologis ibu sendiri. Kurangnya pengetahuan ibu menyebabkan ibu tidak bisa mengenali perubahan fisik yang menjadi kendala dalam menyusui. Penelitian ini bertujuan untuk mengembangkan sistem pakar yang mampu mendiagnosa penyulit menyusui dengan menerapkan metode certainty factor. Tahapan pengembangan sistem pakar meliputi analisis kebutuhan, pengumpulan data, akuisis pengetahuan, representasi pengetahuan, perancangan dan implementasi. Uji akurasi dengan matrik konfusi digunakan untuk mengetahui tingkat keakuratan sistem pakar yang dikembangkan. Hasilnya sistem pakar sudah mampu mendiagnosa gejala penyulit menyusui dengan akurat dan valid.Kata Kunci : Sistem pakar, Certainty Factor, Ibu Menyusui